Policy of the Republic of Kazakhstan in the field of sustainable development - Kassymzhanova, N.A.; Dutta, M. (Вестник Карагандинского университета, 2016)
The article considers the policy of the Republic of Kazakhstan in the field of sustainable development in the conditions of the economic crisis, which has shown in this matter that balance of economy, ecology and social sphere is important. It analyzes the three major national initiatives such as the «Green Bridge», «Green economy» and the «Global energy-ecological strategy of sustainable development in the XXI century». In this article studied the basic legal documents of the Republic of Kazakhstan in the field of sustainable development and an assessment of activities in support of the UN's work in all areas.
Keywords: sustainable development; Green bridge; Green economy; energy-ecological strategy; UN; economics; ecology; social sphere; policy